2020
DOI: 10.3389/fgene.2020.578523
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Variants Potentially Associated With SARS-CoV-2: A Multi-Population Analysis

Abstract: Background Clinical outcomes of coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) showed enormous inter-individual and inter-population differences, possibly due to host genetics differences. Earlier studies identified single nucleotide polymorphisms (SNPs) associated with SARS-CoV-1 in Eastern Asian (EAS) populations. In this report, we aimed at exploring the frequency of a set of genetic polymorphisms that could affect SARS-CoV-2 susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…It has been suggested that the variability in SARS-CoV-2 infection prevalence and COVID-19 mortality in different populations depend largely on individual variations in genes that encode proteins relevant in viral pathogenicity mechanisms. Bioinformatics, case-control and GWAS studies have shown polymorphisms located in several genes as possible susceptibility markers for COVID-19 infection and severity in several populations [ [47] , [48] , [49] , [50] , [51] ]. Located in the 2p24.3 region, the gene that encodes DPP4 is polymorphic and some of its SNPs have been associated not only with the risk of developing some diseases, such as myocardial infarction [ 18 ], rheumatoid arthritis [ 52 ], and T2DM [ 17 ], but also with variations in levels of DPP4 [ 17 ] and apolipoprotein B [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the variability in SARS-CoV-2 infection prevalence and COVID-19 mortality in different populations depend largely on individual variations in genes that encode proteins relevant in viral pathogenicity mechanisms. Bioinformatics, case-control and GWAS studies have shown polymorphisms located in several genes as possible susceptibility markers for COVID-19 infection and severity in several populations [ [47] , [48] , [49] , [50] , [51] ]. Located in the 2p24.3 region, the gene that encodes DPP4 is polymorphic and some of its SNPs have been associated not only with the risk of developing some diseases, such as myocardial infarction [ 18 ], rheumatoid arthritis [ 52 ], and T2DM [ 17 ], but also with variations in levels of DPP4 [ 17 ] and apolipoprotein B [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These events are absent in asymptomatic or patients with milder symptoms. Studies also state that certain immune responsive genes like AHSG, CCL5, CCL2, IL4 variants have a role in disease severity [143].…”
Section: Host Geneticsmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in the gene TMPRSS2 (chromosome 21q22.3, reverse strand) have been associated with susceptibility to and severity of H1N1 or H1N9 influenza A virus infections ( Cheng et al, 2015 ). Currently, SNPs altering gene expression or protein function are frequently discussed in the light of Coronavirus disease 2019 (COVID-19) in literature reviews and in in silico analyses utilizing genotyping data from existing databases ( Asselta et al, 2020 ; Barash et al, 2020 ; Fujikura and Uesaka, 2020 ; Ghafouri-Fard et al, 2020 ; Hou et al, 2020 ; Paniri et al, 2020 ; Russo et al, 2020 ; Senapati et al, 2020 ; Singh et al, 2020 ; Smatti et al, 2020 ; Vargas-Alarcón et al, 2020 ; Zarubin et al, 2020 ). Three variants, rs2070788, rs383510, and rs12329760, seem to be of particular interest based on preliminary work in the context of other virus infections.…”
Section: Introductionmentioning
confidence: 99%